University students perception towards hipster café in kota bharu, kelantan - Nur Afiqah Ariffin; Nur Anis Aqilah Suhaimi; Nor Zahirah Mustafa; Muhammad Syahir Danish Sopiri (2022)
Hipster café has gotten a lot of attention from university students. Kota Bharu is also one of the district that has seen a increase in the number of hipster cafés, which has taken the populace by surprise. With the advent of hipster cafes in Malaysia's coffee industry, hipster cafe operators are strategically spreading their wings in order to capture market share and obtain a competitive advantage over competitors. Customers will favour a hipster cafe that can offer higher-quality items and customer service. This study investigated the impact of Hipster Cafe Services, Culture, and Café Environment on University Students' Perceptions Towards Hipster Cafes in Kota Bharu. The main data for the study will be collected using a structured questionnaire, and the analysis used SPSS version 27 software. The survey was distributed to 384 respondents of students perception towards hipster café. It is possible to conclude that cafe services, culture, and café environment have a considerable favourable impact on students' perceptions of hipster cafes. Keywords: Hipster Café, Café Services, Hipster, Culture, Café Environment , Students Perception